O significado de saúde e doença para o aluno de medicina ao longo da graduação - Lerman, Tatiana Gottlieb [UNIFESP] (2010)
The concepts of medical students about health and illness in the early graduation depends on your knowledge and past experiences as well as the degree of contact with medical practice and the reality that surrounds this issue. The aim of this study was to understand the vision of health and illness that pervades the minds of future doctors and delineate the relationships established between the notion of health and illness, the school curriculum, personal experiences and trajectory of social and professional student throughout the course. It was conducted a qualitative study, using a psychosocial questionnaire and semi-structured interviews with students from first, third and sixth year 2008 the Federal University of São Paulo (UNIFESPEPM). The material was subjected to content analysis. The experiences and personal characteristics of each participant, as well curricular and extracurricular experiences, and the hidden curriculum influence both the vision they hold for health and disease as their career choice. We can note certain coldness in the doctor-patient relationship, and greater distrust of patients throughout the course. Students graduating demonstrate a need to protect the feelings aroused by the experiences during the medicine course. It is clear that students have the knowledge of global and human care patients. However, it seems that they know cognitively, but emotionally they could not put it into practice. This issue would be linked to fact that they are having difficulty contacting these aspects in themselves.